AirNet: An Edge‐Fabric abstraction model to manage software‐defined networks. Issue 6 (25th July 2017) - Aouadj, Messaoud; Lavinal, Emmanuel; Desprats, Thierry; Sibilla, Michelle
Summary: Software‐defined networking (SDN) is one of the most significant initiatives to make current networks easier to configure, test, debug, and evolve. Within an SDN ecosystem, the Northbound interface is used by operators to define policies and to program the control plane, it thus represents a major challenge. Ideally, this northbound interface should allow administrators to describe, as simply as possible, network services and their interactions, rather than specifying how and on what physical device they need to be deployed. In this article, we propose a new network control language, called AirNet, which is built on top of an abstraction model whose main feature is to provide a clear separation between edge and core network devices. Thus, logical boundaries between different types of policies will exist (control, data, and transport services), ensuring modularity and reusability of the control program. An implementation of the AirNet language has also been done, which includes in particular a hypervisor that achieves the composition of the control policies on the virtual network and their mapping on the physical infrastructure. Finally, several experiments showing promising results have been conducted on different use cases. Abstract : AirNet is a novel network control language built on an edge‐fabric abstraction model. It allows network operators to define their own virtual network and to specify control, data, and transport policies on top of it. Logical boundaries exist between these different types of policies, ensuring modularity and reusability of the control program. A runtime system (hypervisor) performs the composition of the control policies, their mapping and deployment on the target physical infrastructure.